University of Calgary : Digital Collections - University of Calgary - Libraries (2021)
"We work closely with subject experts to create: • Unique digital collections that showcase University of Calgary library, museum, and archival primary holdings in many formats • Collections of interest to Albertans and Canadians • Educational resources for use across the curriculum. Please note that the language, terminology or visual content in our historical collections reflect the context and culture of the time of its creation, and may include culturally sensitive information. As an historical document, its contents may be at odds with contemporary views and terminology." [self-description]